Effect of Bilge Keels Position On Roll Motion Performance Of Traditional Wooden Boat - Muhammad Akbar Asis; Daeng Paroka; Syamsul Asri; Muhammad Anjas Syam (International Journal of Marine Engineering Innovation and Research, 2020)
The most ship accidents occurred on size between 35GT and 500GT, including traditional wooden boats. The accidents were dominated by capsizing due to bad weather. Therefore the safety of traditional wooden boats needs to be improved. This paper discusses the position of bilge keels and their impact on the roll motion performance of an Indonesian traditional wooden boat. The roll damping is determined by a roll decay test with three different positions of bilge keels, namely 15 degrees, 30 degrees, and 45 degrees. The roll amplitude is determined in the frequency domain by solving the uncoupled nonlinear roll motion equation with an effective wave slope coefficient calculated using the simplified Froude-Krylov assumption of roll exciting moment. The bilge keels position with the angle of 15 degrees reduced the roll amplitude of 18% while the position with an angle of 30 degrees decreases the roll amplitude by 7% of roll amplitude without bilge keels. The bilge keels position with an angle of 45 degrees reduced the roll amplitude by 2% of those without bilge keels. The natural roll period was not significantly affected by the bilge keels position. The bilge keels position with an angle of 15 degrees is the most effective position to reduce the roll amplitude.